The Mood Rhythm Instrument: development and preliminary report - Camila M. de Souza; Alicia Carissimi; Daniele Costa; Ana Paula Francisco; Madeleine S. Medeiros; Carlos A. Ilgenfritz; Melissa A. de Oliveira; Benicio N. Frey; Maria Paz Hidalgo (Brazilian Journal of Psychiatry, 2016)
Objective: To describe the initial steps in the development and validation of a new self-reported instrument designed to assess daily rhythms of mood symptoms, namely, the Mood Rhythm Instrument. Methods: A multidisciplinary group of experts took part in systematic meetings to plan the construction of the instrument. Clarity of items, their relevance to evaluation of mood states, and the consistency of findings in relation to the available evidence on the biological basis of mood disorders were investigated. The internal consistency of the questionnaire was evaluated through Cronbach’s alpha. Results: All of the items proposed in a first version were well rated in terms of clarity. The items more frequently rated as “rhythmic” were related to the somatic symptoms of mood. Their peaks in 24 hours were more frequent in the morning. The items associated with affective symptoms of mood were rated as less rhythmic, and their peak in 24 hours occurred more frequently in the afternoon and evening. Males and females behaved more similarly with respect to somatic than behavioral-affective items. The second version of the Mood Rhythm Instrument had a Cronbach’s alpha of 0.73. Conclusion: The proposed Mood Rhythm Instrument may be able to detect individual rhythms of cognitive and behavioral measures associated with mood states. Validation in larger samples and against objective measures of rhythms, such as actigraphy, is warranted.